The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s000711452100129x
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status of postpartum women and their infants aged 3, 6 and 12 months: Mother and Infant Nutrition Investigation (MINI)

Abstract: To alleviate the re-emergence of iodine deficiency in New Zealand, two strategies, the mandatory fortification of bread with iodised salt (2009) and a government-subsidised iodine supplement for breastfeeding women (2010) were introduced. Few studies have investigated mother and infant iodine status during the first postpartum year, this study aimed to describe iodine status of mothers and infants at three, six, twelve months postpartum (3MPP,6MPP,12MPP). Partitioning of iodine excretion between urine and brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…It should be noted that disinfectants used during cesarian delivery may contain iodine and unintentionally exaggerate the BMIC in colostrum ( 281 ). A modest decline in BMIC over the course of lactation has been reported in longitudinal studies at low ( 276 , 282 ), adequate ( 255 , 256 ), and high iodine intakes ( 19 , 280 ), although not all studies agree ( 283 ). Cross-sectional studies indicate a similar trend ( 19 , 247 , 254 ) but results are mixed ( 203 , 258 ).…”
Section: Iodine In Human Milkmentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that disinfectants used during cesarian delivery may contain iodine and unintentionally exaggerate the BMIC in colostrum ( 281 ). A modest decline in BMIC over the course of lactation has been reported in longitudinal studies at low ( 276 , 282 ), adequate ( 255 , 256 ), and high iodine intakes ( 19 , 280 ), although not all studies agree ( 283 ). Cross-sectional studies indicate a similar trend ( 19 , 247 , 254 ) but results are mixed ( 203 , 258 ).…”
Section: Iodine In Human Milkmentioning
confidence: 98%
“…Maternal fluid intake influences the iodine concentration in urine, but has less impact on BMIC ( 249 ). The fractional iodine excretion in breast milk and urine may vary depending on the iodine intake and iodine status ( 250 , 276 ). We conducted an observational study in iodine-sufficient populations and found that proportionally more iodine is excreted in breast milk (two-thirds) than in urine (one-third) at low iodine intake compared to higher intake ( 250 ).…”
Section: Iodine In Human Milkmentioning
confidence: 99%
“…A trend toward a moderate decrease in BMIC over the course of lactation has been found in longitudinal studies in iodine-deficient areas (22,23), iodine-sufficient areas (8, 24), and iodine-excessive areas (25). We also observed a gradual decrease in median BMIC with increasing infant age and body mass from 5 to 26 weeks postpartum.…”
Section: Discussionmentioning
confidence: 81%
“…The researchers found that in iodine-sufficient countries, as iodine intake decreased, iodine was increasingly partitioned into breast milk, and hence, the fraction of iodine in urine decreased, whereas in the iodine-deficient country, the proportion in of iodine in breast milk remained constant. A small New Zealand study ( n = 87) found a similar variance in partitioning of iodine between breast milk and urine dependent upon status [ 19 ]. Further, a recent Iranian study found that although maternal UIC and BMIC were associated with neonatal UIC, BMIC was the stronger predictor of neonatal UIC [ 20 ].…”
Section: Challenges Of Defining Iodine Statusmentioning
confidence: 99%
“…Using daily iodine supplementation to address deficiency has limitations as there are several barriers to supplement use and uptake is often less than optimal [ 62 ]. In small New Zealand studies of educated women, iodine supplement use ranged from 6 to 40% among breastfeeding women and reduced with infant age [ 19 ]; deficiency was evident among non-users of supplements. Iodine supplement use is also lower among mothers who are younger and less educated and among some ethnic groups (Māori or Pacifica in New Zealand and Indigenous Australians) [ 63 , 64 ].…”
Section: Treatment Of Iodine Deficiency: Universal Salt Iodization Ve...mentioning
confidence: 99%